2018
DOI: 10.1016/j.pediatrneurol.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

A Modern Epidemic: Increasing Pediatric Emergency Department Visits and Admissions for Headache

Abstract: OBJECTIVE:Headaches represent 0.9% to 2.6% of visits to a pediatric emergency department (PED). We noted a trend of increasing visits for headache in our tertiary care PED and sought to further characterize this trend. METHODS:We identified PED visits with International Classification of Disease, Ninth Revision, Clinical Modification diagnoses for headache at 25 hospitals in Pediatric Health Information System between 2003 and 2013. To further characterize demographics and treatment trends over time we used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Headache in children and adolescents is a growing medical but also social task. This is supported on the one hand by the increasing use of medical facilities by children and adolescents with headaches in recent years, as shown in data from South Korea, Italy, and the USA [11][12][13]. On the other hand, various studies have investigated headache prevalence, mostly in school-based cross-sectional studies, with the conclusion that there is a high prevalence of headache in children and adolescents globally (Fig.…”
Section: Recent Studies On Headache Prevalencementioning
confidence: 96%
“…Headache in children and adolescents is a growing medical but also social task. This is supported on the one hand by the increasing use of medical facilities by children and adolescents with headaches in recent years, as shown in data from South Korea, Italy, and the USA [11][12][13]. On the other hand, various studies have investigated headache prevalence, mostly in school-based cross-sectional studies, with the conclusion that there is a high prevalence of headache in children and adolescents globally (Fig.…”
Section: Recent Studies On Headache Prevalencementioning
confidence: 96%
“…In the United States, up to 1-4% of emergency department visits is caused by headache [2,3]. Recently, a study on selfreported migraine or severe headache in the United States shows that approximately one in six Americans has been affected by headache in the past three months, and one in ve women has been affected by headache [4].…”
Section: Introductionmentioning
confidence: 99%
“…Headache is a frequent reason for children and young adults to present to the emergency department. 1,2 In the emergency department, health care providers are tasked with distinguishing primary versus secondary headaches. Findings from retrospective 1,3 -5 studies suggest that between 2% and 15% of pediatric patients with headache evaluated in the emergency department have an underlying serious etiology.…”
mentioning
confidence: 99%
“…The investigations of headache in children and young adults have largely been limited to pediatric emergency departments, 2,3,13 -15 which represent a small fraction of overall emergency department encounters in this population. One prior investigation of 43 pediatric emergency departments suggested that rates of headache presentation were rising over time.…”
mentioning
confidence: 99%
See 1 more Smart Citation